MANUFACTURING AND TESTING THE VALIDITY AND RELIABILITY OF PARENTS KNOWLEDGE LEVEL MEASURMENT TOOLS ON ORAL CADIDIASIS IN INFANTS AGE 0-12 MONTHS - Fatimah Alaydrus; Rina Kartika Sari; Welly Anggarani; Musri Amurwaningsih (Jurnal Medali, 2023)
Background: Oral candidiasis is a fungal infection that affects the oral mucosa, most of these lesion are caused by Candida albicans. Candida infection often occured in infants aged 0-12 months because they had imunoregulator system which hadnot matured completely. Other causes were parents who often gave milk through bottles, leftover milk in the baby's mouth that was not cleaned, bad habits by giving pacifiers (fopspeen) to suck without paying attention to cleanliness.. The role of parents was very important in maintaining to prevent oral candidiasis. Make a valid and reliabel measured instrument in the form of a questionnaire is needed to be able to measeure the level of parental knowledge of oral candidiasis, until now there is no instrument that measure this focus. The main purpose in this study was to create a valid and realiable instrument which measure the level of parental knowledge of oral candidiadis in infants aged 0-12 months. Method: The study method is descriptive stages were the preparation of dimensions, indicators and statement items, content validity index(CVI), construct validity test with pearson correlation test (rcount>rtable) and reliability test by looking at the cronbach alpha value(0>7). Result: Results showed a valid I-CVI mean value was 0.89, the construct validity test showing the correlation value of each item was greater than 0.361 and the reliability stage showing the Cronbach Alpha value of 0.902 was greater than 0,7. Conclusion: : It was concluded that the contained 28 items of instrument statements on the level of parental knowledge of oral candidiasis in infants aged 0-12 months, valid and reliable,according to the principle that can be used as a measuring tool for further study